Loghat kelate vs ganu / Wan Anisha Wan Mohammad... [et al.] - Wan Mohammad, Wan Anisha; Mohamed Yusoff, Syarifah Adilah; Mohd Mydin, Azlina; Johan, Elly Johana (Unit Penerbitan Dan Publisiti JSKM, 2022)
Loghat kelate vs ganu